Industry-Level Female-Male Wage Gap in Turkey - Mercan, Murat Anil; Karakas, Mesut (Ahmet Yesevi Univ, 2015)
Inter-industry wage differentials between women and men have received increasing attention in the literature, but few studies have examined this phenomenon for developing countries. This study investigates the female-male wage differentials for Turkey, which is an eastern and developing country. A simple Blinder-Oaxaca type decomposition analysis of the female-male inter-industry wage differential suffers mainly from identification problems. Therefore, we use a new approach to overcome these problems. Our results suggest that the female-male wage gap in the Turkish labor market is relatively high and in favor of males in human health activities, education activities, and financial service activities (except insurance and pension funding). Also, it is generally small among other industries. A possible explanation for this fact is that the female labor force participation rate is low in these sectors in Turkey.
Keywords: labor market; inter industry wage differentials; female-male wage differential; wage discrimination; gender-wage decomposition; Turkey